Religious coping and perceived social support in explaining effects of trait emotional intelligence to ameliorate the psychosocial stress among students - Rashid, Ifza Abdul (Mental health, religion & culture, 2024)
The current study examined the roles of positive religious coping and perceived social support in explaining the effects of trait emotional intelligence (EI) on psychosocial stress among students while transitioning from online to on-campus mode of learning. A cross-sectional survey research design was used to recruit both samples (n = 171 adolescent and n = 185 adult students). A set of psychological measures was administered to collect information regarding demographic variables, psychosocial stress, perceived social support, trait EI and positive religious coping. The results indicated a significant relationship among perceived social support, positive religious coping, trait EI and psychosocial stress. Moreover, it was found that the inverse relationship between trait EI and psychosocial stress was mediated fully by perceived social support. Our findings underscore valuable information for academics and the community of Pakistan as it provides awareness regarding trait EI and perceived social support as coping mechanisms while dealing with stressful situations.